The meaning of “concept” in Linguistics - Ruzieva Khayotkhon Bakhodir Qizi; Umirziyaev Umidjon Makhamadjonovich (Zien Journals, 2022)
The research is focused on the analysis of one of today's developing fields, cognitive linguistics, and one of its theoretical notion of ‘’concept’’. The object of the study is to show some ideas based on the meaning of “concept” and its analysis and to clarify its importance in cognitive linguistics.
Keywords: linguistics; linguocultural; ethnocultural; development